Moderating role of religious beliefs on attitudes towards charities and motivation to donate. Issue 5 (4th November 2014) - Teah, Min; Lwin, Michael; Cheah, Isaac
Abstract : Purpose: – The purpose of this paper is to examine the relationship between image of charitable organizations, attitudes towards charities and motivation to donate. In addition, the study will investigate the moderating effects of religious beliefs on attitudes towards charities and motivation to donate. Design/methodology/approach: – Data are collected using a self-administered questionnaire. Trained interviewers employed a mall-intercept method in downtown Kuala Lumpur over both weekdays and weekends. The scales are adapted from established sources. Findings: – It was found that religious beliefs moderates the relationship between attitudes towards charities and motivation to donate. In addition, image of charitable organizations has a positive influence on attitudes towards charities. It was also found that both image of charitable organizations and attitudes towards charities influence motivation to donate. Research limitations/implications: – The study is conducted within downtown Kuala Lumpur and is not generalizable across Malaysia and other countries. In addition, this study only looked at general religious beliefs, therefore findings are not specific to a religion. As a result, possible religious differences may be neglected. Lastly, the study only focused on donors and further studies need to be conducted on non-donors to further understand donation behaviour. Practical implications: – The findings from the study provide valuable insights to charities, government bodies and policy makers as it highlights the linkages between image of charitable organizations, attitudes towards charities and the motivation to donate of past donors. Additionally, religious bodies can also use the findings to formulate communication strategies to benefit charities as well as the broader community. Originality/value: – The study provides insights into the motivations of donors to donate to charities. More importantly, it also examines the influence of religious beliefs on donation behaviour, thus shedding insights on the opportunities for fundraising by charities.